PD-1 regulates leishmanicidal activity and IL-17 in dogs with leishmaniasis - Rebech, Gabriela Torres [UNESP]; Venturin, Gabriela Lovizutto [UNESP]; Siqueira Ito, Lucas Takeshi [UNESP]; Bragato, Jaqueline Poleto [UNESP]; de Carvalho Fonseca, Bianca Stefanini [UNESP]; Melo, Larrissa Martins [UNESP]; Costa, Sidnei Ferro [UNESP]; de Rezende Eugênio, Flávia [UNESP]; dos Santos, Paulo Sérgio Patto [UNESP]; de Lima, Valéria Marçal Felix [UNESP] (Elsevier, 2020)
Leishmaniasis is an immunosuppressive disease caused by protozoa of the genus Leishmania, for which dogs are the domestic reservoir. The programmed cell death-1 molecule (PD-1) is highly expressed in leukocyte cells of dogs with leishmaniasis, and it promotes T lymphocyte exhaustion and suppression of cytokine secretion. Because PD-1 has a suppressive function regarding cell immunity, we evaluated the effect of PD-1 blocking antibodies on NO, ROS and interleukin 17 (IL-17) production and on parasite load in spleen leukocyte cultures from dogs with leishmaniasis. In vitro, PD-1 blocking promoted increased levels of intracellular NO and NO2 and reduced the levels of IL-17 in the culture supernatant, in addition to reducing the parasite load, but it did not change ROS levels. We conclude that PD-1 participates in the regulation of the immune response and that the blocking antibody is effective in restoring host microbicidal activity. This can be investigated in an immunotherapeutic study in the future.
Keywords: CD279; Cytokines; Protozoa; Spleen leukocytes